Peran Guru PAI dan Guru Bimbingan Konseling dalam Mendisiplinkan Siswa Madrasah Aliyah - Ellistiyawati, Azidah; Nasrul Amin, Moh. (Darajat: Jurnal Pendidikan Agama Islam, 2022)
Every student certainly needs discipline, because with discipline students can behave not deviate. With discipline students show good behavior and obey the rules and comply with various rules and regulations. Such as arriving on time to school, entering class first, and wearing school attributes according to regulations. Of all that, of course there are some students who commit disciplinary actions. Therefore, the role of the PAI teacher and guidance and counseling teacher is interrelated so that students can be trained and controlled with appropriate teachings. This research focused on the role of Islamic religious education teachers and guidance and counseling teachers in disciplining MA Mazra'atul Ulum students with the following problem formulation: First, the role of Islamic religious education teachers and guidance and counseling teachers in disciplining MA Mazra'atul Ulum students. Second, the inhibiting factors of Islamic religious education teachers and guidance and counseling teachers in disciplining MA Mazra'atul Ulum Paciran students. To achieve this goal using a qualitative descriptive method. The subjects of this study were Islamic religious education teachers and guidance and counseling teachers at MA Mazra'atul Ulum Paciran. Data collection techniques in this study are observation, interviews and documentation. The results of the study show that: The role of the Islamic religious education teacher is very important in disciplining students not only as a provider of material, but as a guide, as an example and role model, as a motivator. Meanwhile, the role of guidance and counseling teachers in disciplining students is as a punisher, as a motivator, and as a director. The inhibiting factors for Islamic religious education teachers, limited supervision of teachers, and factors from students. Meanwhile, the inhibiting factors for guidance and counseling teachers in disciplining students are factors from students such as students' lack of attention to the importance of discipline in school rules.